Research on Process Mineralogy of Titanium-Bearing Blast Furnace Slag in Panzhihua-Xichang Area - Xu Guoyin; Wang Purong (E3S Web of Conferences)
Titanium-bearing blast furnace slag is an important resource among the by-products of the steel industry, and the recycling of titanium elements holds significant economic and environmental importance. This study conducts a detailed process mineralogy analysis of Panzhihua-Xichang titanium-bearing blast furnace slag samples, exploring the mineral composition, occurrence state of titanium elements, the dissemination characteristics and particle size distribution of the main titanium-bearing minerals, as well as micro-area composition analysis of titanium elements. The research findings indicate that ilmenite and perovskite are the primary titanium-bearing minerals in the samples, with titanium elements mainly residing in these two minerals. Through analysis of the particle size distribution and degree of liberation, potential pathways for enhancing the recovery rate of titanium elements are proposed, providing a theoretical basis for the resource utilization of titanium-bearing blast furnace slag.